Development of website-based culinary art learning media in improving practical skills in the culinary arts study program - Fridiarty, Lelly; Putri, Yuzia Eka; Anugerah, Ajeng Inggit; Waruwu, Mawadda Azizah Sari (International Journal for Educational and Vocational Studies, 2022)
This study is motivated by a lack of expertise in curving practice after learning theoretically. Of course, this makes learning conditions very difficult and ineffective with insufficient theoretical material to provide guidance to students in practice. Therefore, the research was conducted to develop a website-based learning media that can be accessed anytime and anywhere with the aim of improving curving skills in culinary arts courses. In this study, the Sugiyono development model has been simplified, the steps are:  (1) preliminary studies, (2) Product design, (3) Product Validation, (4) Product revision, (5) Product trial, (6) The final product. The sample in this study were students of the 3rd semester of the Catering Study Program. The sample in this study were students of the 3rd semester of the Catering Study Program. Data analysis techniques by analyzing the results of media and material expert validation questionnaires and analyzing the effectiveness of website media on students. It is known from the research results, website-based learning media in Culinary Arts courses are good and feasible to use.